Sperm binding to ZP2-coated beads improve the efficiency of porcine in vitro fertilisation. Issue 5 (November 2020) - Gabriela Hamze, Julieta; Jiménez-Movilla, María; Romar, Raquel
Abstract : The role of specific zona pellucida (ZP) glycoproteins in gamete interaction has not yet been elucidated in many species. A recently developed 3D model based on magnetic sepharose beads (B) conjugated to recombinant ZP glycoproteins (BZP ) and cumulus cells (CBZP ) allows the study of isolated ZP proteins in gamete recognition studies. The objective of this work was to study the role of porcine ZP2, ZP3 and ZP4 proteins in sperm binding, cumulus cell adhesion and acrosome reaction triggering. ZP protein-bound beads were incubated with fresh ejaculated boar spermatozoa and isolated cumulus cells for 24 h. The number of sperm bound to the beads, the acrosomal shrouds (presence of acrosomal content) on the bead's surface, and the acrosome integrity (by means of PNA-FITC lectin) in bound and unbound sperm were studied. Finally, in vitro matured porcine oocytes mixed with BZP2 were inseminated in vitro using fresh sperm and fertilisation results evaluated. Over 60% of beads had at least one sperm bound after 2 h of coincubation. ZP2-beads (BZP2 ) and cumulus-ZP2-bead complexes (CBZP2 ) reached the highest number of sperm per bead, whereas BZP3 and BZP4 models showed the highest number of unbound reacted sperm cells and acrosomal shrouds. Fertilisation efficiency and monospermy rate increased when oocytes were fertilised in the presence of BZP2 . We, therefore, conclude that in pigs, it is mainly ZP2 that is involved in sperm-ZP binding whereas ZP3 and ZP4 induce acrosome reaction. Using magnetic sepharose ZP2-bound beads might be a valuable tool to improve the fertilisation rate in pigs.